2009
DOI: 10.1113/expphysiol.2009.049023
|View full text |Cite
|
Sign up to set email alerts
|

Relative proportions of hybrid fibres are unaffected by 6 weeks of running exercise in mouse skeletal muscles

Abstract: Hybrid muscle fibres co-expressing two or more myosin heavy chain (MHC) isoforms represent a significant proportion of fibres in many muscles, but the prevalence and precise composition of these fibres varies significantly among muscles and animal species. In the present study, we used a forced running protocol for 6 weeks to determine the effects of running exercise on the relative proportion of hybrid muscle fibre types in mouse muscles. In the course of this experiment, we also determined the relative propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 50 publications
4
47
1
1
Order By: Relevance
“…1 ). This pattern is different from the results reported for rodent MHCs in other studies [Talmadge and Roy, 1993;Di Maso et al, 2000;Caiozzo et al, 2003;Glaser et al, 2010] in that the IIA and IIX isoforms are reversed in their migration order. As we have indicated previously, the result is better separation of the IIA and IIX isoforms .…”
Section: Proportions Of Fiber Types In Ta Br and Sol Musclescontrasting
confidence: 56%
See 2 more Smart Citations
“…1 ). This pattern is different from the results reported for rodent MHCs in other studies [Talmadge and Roy, 1993;Di Maso et al, 2000;Caiozzo et al, 2003;Glaser et al, 2010] in that the IIA and IIX isoforms are reversed in their migration order. As we have indicated previously, the result is better separation of the IIA and IIX isoforms .…”
Section: Proportions Of Fiber Types In Ta Br and Sol Musclescontrasting
confidence: 56%
“…In mouse, the overall fiber type distribution is lower than in the rat, being highly skewed toward the fastest IIB fiber type. Nevertheless, certain mouse muscles contain 25-50% of their fibers as hybrids [Glaser et al, 2010;Zhang et al, 2010]. In the muscles of both of these rodents, the most prevalent hybrid fiber types are the IIX/IIB hybrids, which represent roughly 70-90% of all the hybrid fibers [Caiozzo et al, 2003;Glaser et al, 2010;Zhang et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy between EDL and soleus muscles in the reliance of MLCK on E 2 -induced pRLC could be related to different abundances of MLCK and myosin light chain phosphatase proteins and their activities in the two muscles (50), differences in cellular context for ER-mediated signaling pathways, or myosin isoform differences between the two muscles. In regard to the latter, there is fiber type heterogeneity in the mouse soleus muscle as is it comprised of type I and IIa fibers based on myosin heavy chain isoform expressions (13), whereas mouse EDL muscle is more homogeneous, with only type II fibers (52), and it has been demonstrated that potentiation is greater in type II than in type I fibers (60). How the effects of E 2 may differ among fibers with various isoforms of the myosin heavy and light chains is not presently clear, nor is the impact of estrogen status on expression of the various myosin isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical load (13,15), denervation (41,(63)(64)(65), spinal cord transection (63)(64)(65), hormonal manipulation (13,15,19), and chronic electrical stimulation (47) are each capable of producing major changes in the hybrid fiber content of skeletal muscles. The influence of more natural interventions, like aging and exercise, on hybrid skeletal muscle fibers generally appears to be much less dramatic (7,25,27,29,68,69). As data from skeletal muscles under a variety of conditions have accumulated, it has become clear that hybrid fibers often represent stable phenotypes and are common components of normal muscles (16,60).…”
mentioning
confidence: 98%